ST‐segment elevation on intracoronary electrocardiogram after percutaneous coronary intervention is associated with worse outcome in patients with non‐ST‐segment elevation myocardial infarction. Issue 4 (8th July 2015) - Hishikari, Keiichi; Kakuta, Tsunekazu; Lee, Tetsumin; Murai, Tadashi; Yonetsu, Taishi; Isobe, Mitsuaki
Abstract : Objectives: We sought to examine whether intracoronary electrocardiogram (IC‐ECG) assessment in patients with non‐ST‐segment elevation myocardial infarction (NSTEMI) can predict cardiac outcomes. Background: There has been no data correlating myocardial damage and cardiac events with an IC‐ECG ST‐segment change after percutaneous coronary intervention (PCI) in NSTEMI patients. Methods: We examined 111 NSTEMI patients undergoing PCI with an IC‐ECG recording. IC‐ECG ST‐segment elevation (STE) was defined as >0.1 mV in the risk area, located by placing the guidewire distal to the culprit lesion. Clinical characteristics and in‐hospital and long‐term follow‐up adverse cardiac event rates were compared between IC‐ECG STE and non‐IC‐ECG STE groups at the completion of PCI. Results: IC‐ECG STE was observed in 36 patients (32.4%) immediately after PCI. Peak cardiac biomarkers were significantly elevated in patients with IC‐ECG STE versus those without (cardiac troponin I 31.9 ng/mL (18.0–104.5) vs. 8.2 ng/mL (1.8‐21.4); P < 0.001). At a median follow‐up of 35 months, the cardiac event free rate was significantly worse in patients with IC‐ECG STE than in those without (long‐rank test χ 2 = 10.9; P = 0.001). Cox proportional hazards analysis showed IC‐ECG STE (hazard ratio, 2.54; 95% confidence interval [CI], 1.38–4.70; P = 0.003) was an independent predictors of cardiac events. Conclusions: The present study suggests that presence of IC‐ECG STE might help identify high‐risk NSTEMI patients with greater myocardial injury leading to adverse cardiac events. © 2015 Wiley Periodicals, Inc.